Building Smart Villages melalui SIMPELDESA: Menuju Dynamic Governance di Sidoarjo - Rani, Berliana Mustika (Universitas Medan Area, 2025)
This article aims to examine the implementation of the SIMPELDESA program as a digital innovation in village governance in Sidoarjo Regency. The study focuses on the effectiveness, service impact, governance transformation, service inclusivity, and the potential for replication of SIMPELDESA as a Smart Villages model. To approach this issue, the study applies theoretical frameworks from Smart Villages, Public Service, and Dynamic Governance. Data were collected through in-depth interviews, field observations, and document analysis in selected recipient villages and were analyzed qualitatively. The findings indicate that SIMPELDESA improves the efficiency and transparency of village public services, strengthens the capacity of village officials in adopting digital innovations, and fosters a governance culture based on learning and citizen participation. The inclusivity of services for vulnerable groups reflects a paradigm shift toward more responsive and equitable service delivery. The program also shows significant potential for replication in other areas as a sustainable framework for village digitalization. This study concludes that SIMPELDESA serves as a model for digital transformation in village governance that is adaptive and oriented towards community empowerment.